Etanercept embedded silk fibroin/pullulan hydrogel enhance cartilage repair in bone marrow stimulation - Song, Xiongbo; Wang, Xin; Guo, Lin; Li, Tao; Huang, Yang; Yang, Junjun; Tang, Zhexiong; Fu, Zhenlan; Yang, Liu; Chen, Guangxing; Chen, Cheng; Gong, Xiaoyuan (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Bone marrow stimulation (BMS) is the most used operative treatment in repairing cartilage defect clinically, but always results in fibrocartilage formation, which is easily worn out and needs second therapy. In this study, we prepared an Etanercept (Ept) embedded silk fibroin/pullulan hydrogel to enhance the therapeutic efficacy of BMS. Methods: Ept was dissolved in silk fibroin (SF)—tyramine substituted carboxymethylated pullulan (PL) solution and enzyme crosslinked to obtain the Ept contained SF/PL hydrogel. The synergistical effect of SF/PL hydrogel and Ept was verified by rabbit osteochondral defect model. The mechanism of Ept in promoting articular cartilage repair was studied on human osteoarthritic chondrocytes (hOACs) and human bone marrow mesenchymal stromal cells (hBMSCs) in vitro, respectively. Results: At 4 and 8 weeks after implanting the hydrogel into the osteochondral defect of rabbit, histological analysis revealed that the regenerated tissue in Ept + group had higher cellular density with better texture, and the newly formed hyaline cartilage tissue was seamlessly integrated with adjacent native tissue in the Ept + group. In cellular experiments, Ept treatment significantly promoted both gene and protein expression of type II collagen in hOACs, while decreased the protein levels of metalloproteinase (MMP)-13 and a disintegrin and metalloprotease with thrombospondin motifs 5 (ADAMTS5); alcian blue staining, type II collagen and aggrecan stainings showed that addition of Ept significantly reversed the chondrogenesis inhibition effect of tumor necrosis factor alpha (TNF-α) on hBMSCs. Conclusion: BMS could be augmented by Ept embedded hydrogel, potentially by regulating the catabolic and anabolic dynamics in adjacent chondrocytes and enhancement of BMSCs chondrogenesis.